Upaya Pencegahan Tindakan Balapan Ilegal di Kota Sungailiat (Studi Wilayah Hukum Kota Sungailiat) - Lukas Imanuel; Toni Toni; Rio Armanda Agustian (Lembaga Yasin AlSys, 2025)
This study is motivated by the rising phenomenon of illegal street racing, particularly among youth who engage in high-speed competitions on public roads. Such practices pose serious risks to the safety of both participants and other road users, while also disrupting public order. Therefore, systematic and sustainable preventive efforts are urgently needed. The purpose of this research is to examine the forms of preventive measures against illegal street racing in Sungailiat City and to identify the factors influencing the effectiveness of these efforts. The study adopts an empirical juridical approach. The findings indicate that preventive efforts have been implemented in various forms, including public education and awareness campaigns, the